Parklife – Listening to Stories as a Deep Missional Practice - Mann, Sally (Ecclesial Futures, 2022)
This paper offers theological reflections on a sociological research project the author undertook during the 2020 Covid lockdown, called Parklife (Author, 2021). It adopts Riceour’s hermeneutical phenomenology and the concept of the narratological self to explore the potential for transformation in autobiographical stories. In reflecting on stories gathered from a community of people experiencing homelessness it argues that attentive listening has transformational power - an act of soul recreation, the transformation of the self. It grounds its findings in a set of suggestions to shape how we might better attend to stories and become story-rich communities as a missional practice.